Production, Diversity, and Distribution of Aquaculture Commodities in Tuban, Indonesia - Syifania Hanifah Samara; Muhamad Amin; Wahyu Isroni; Veryl Hasan; Muhammad Browijoyo Santanumurti; Muhammad Ar Rozzaaq Nugraha; Muyassar H. Abualreesh (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract